Mediastinal, retroperitoneal, and subcutaneous emphysema due to sigmoid colon penetration: A case report and literature review. (2019) - Muronoi, Tomohiro; Kidani, Akihiko; Hira, Eiji; Takeda, Kayo; Kuramoto, Shunsuke; Oka, Kazuyuki; Shimojo, Yoshihide; Watanabe, Hiroaki
Highlights: Massive mediastinal emphysema is rare signs of colon perforation. The diagnosis may be delayed due to the absence of peritoneal irritation. Laparotomy should be considered in case of colonic penetration with the mediastinum emphysema. Abstract: Introduction: Mediastinal and subcutaneous emphysema usually result from spontaneous rupture of the alveolar wall. We present an extremely rare case of massive mediastinal, retroperitoneal, and subcutaneous emphysema due to the penetration of the colon into the mesentery. Presentation of case: A 57-year-old man presented to our institution with a history of chest pain. The patient's medical history included malignant rheumatoid arthritis during the use of steroids and an immunosuppressive agent. The patient had no signs of peritoneal irritation or abdominal pain. A chest radiography revealed subcutaneous emphysema of the neck, mediastinal emphysema, as well as subdiaphragmatic free air. Computed tomography showed extensive retroperitoneal, mediastinal, and mesenteric emphysema of the sigmoid colon without pneumothorax. Diagnostic laparoscopy was performed and revealed perforation into the sigmoid mesentery. Segmental resection of the sigmoid colon and end-colostomy were performed. The diverticulum was communicating with the outside of the mesentery via the mesentery. The mediastinal emphysema disappeared a few days after the surgery. Discussion: Colonic perforation generally results in free perforation. Colonic gas may spread via various anatomical pathways when perforation of the colon occurs in the retroperitoneum; thus, diverse atypical clinical symptoms may be present. Signs of peritoneal irritation can be hidden in cases of retroperitoneal colonic perforation. The atypical manifestation of a retroperitoneal colonic perforation can cause difficulties in making a diagnosis. Conclusions: Massive mediastinal and retroperitoneum emphysema are rare signs of colonic perforation. Emergency laparotomy should be considered in colonic penetration of the diverticulitis where the emphysema expands to the mediastinum extensively.